Estimation of a Distribution function under Sampling on Two Occasions - Chadyšas, V. (Nonlinear Analysis: Modelling and Control, 2009)
Estimation of the distribution function under sampling on two occasions with a simple random sampling design on each occasion is investigated. Composite regression and ratio type estimators are considered, using values of the study variable as auxiliary information obtained on the first occasion. The optimal estimator, in the sense of minimal variance, is also obtained. A simulation study, based on the real population data, is performed and the proposed estimators are compared by a simple estimator for a distribution function.
Keywords: distribution function; sampling on two occasions; auxiliary information; regression estimator; ratio estimator